Cardiovascular benefits of air purifier in patients with stable coronary artery disease: A randomized single-blind crossover study - Liu, Zhe; Wang, Qin; Li, Na; Xu, Chunyu; Li, Yunpu; Zhou, Jun; Liu, Liu; Zhang, Haijing; Mo, Yang; Han, Feng; Xu, Dongqun (Frontiers in Public Health, 2023)
Background Exposure to PM2.5 will accelerate the progression of cardiovascular diseases. Air purifier can reduce the PM2.5 exposure and theoretically alleviate the influence of PM2.5 on patients with stable coronary artery disease (SCAD). However, few studies of the protective effect showed significant results because the interferent effects of routine medication had not been taken into account. In order to explore the actual effect on patients with SCAD, we conducted a randomized single-blind crossover air purifier intervention trial. Method Levels of PM2.5 exposure during intervention and cardiovascular indicators (inflammation, coagulation, plaque stability, and blood lipids) after intervention were detected, meanwhile the information of drug use was obtained by questionnaire. The kinds of drug used by more than 20% of the subjects were sorted out. And the influence of these drugs on cardiovascular indicators was summarized through literature review. Based on that, the drug use was included as a variable in linear mixed effects models that used to analyze the associations between PM2.5 exposure reduction by air purifier and cardiovascular indicators. Results The result revealed that the interpretation contribution rate of drug use was more than that of PM2.5 exposure. The level of C-reactive protein significantly decreased by 20.93% (95%CI: 6.56%, 33.10%), 23.44% (95%CI: 2.77%, 39.39%) and 24.11% (95%CI: 4.21%, 39.69%) on lag1, lag01 and lag02 respectively, while the level of high-density lipoprotein cholesterol significantly increased by 5.10% (95%CI: 0.69%, 9.05%), 3.71% (95%CI: 0.92%, 6.60%) and 6.48% (95%CI: 2.58%, 10.24%) respectively on lag0, lag1 and lag01 associated with an interquartile range decrease of 22.51 μg/m3 in PM2.5 exposure. Conclusion The study shows positive effects of air purifier on SCAD, and also provides methodological reference for future related research.